A Theoretical Rationale why Furan‐side Monoadduct is More Favorable Toward Diadduct Formation in 8‐Methoxypsoralen and Thymine Complexes. (4th April 2013) - Huang, Xuebin; Zhang, Rubo
Abstract The photoinduced mechanism of formation of mono‐ and diadducts between 8‐MOP and thymine bases is studied using the ONIOM(MPWB1K/6–31 + G(d, p):B3LYP/6–31G(d, p):UFF) and B3LYP/6–31 + G(d, p) methods. The relevant cycloaddition displays favorable energy barriers and reaction energies in the triplet excited state, which involves the initial formation of a diradical followed by ring closure via singlet–triplet interaction. The monoadduct on the pyrone side is favored over the furan side when comparing reaction energies. The distinguishing feature in the formation of the monoadducts is that the furan‐side adduct displays a better photostability, which is a relatively high‐barrier exothermic reaction, and thus the energy balance of the monoadduct on the furan side toward final diadduct formation is favored.